Socio Cultural Perspective on a Formation of Peri Urban Identity in Kuala Selangor Region, Malaysia - Mazlan, Maizura; Atiah Ismail, Nor; Abdul Aziz, Faziawati; Johari Mohd Yusof, Mohd (International Journal of Engineering and Technology, 2026)
At present time, Malaysia gradually undergoes a pace of urban and rural transformation. The rapid growth of cities in Malaysia expand-ing beyond their incorporation boundaries transformed the land use from rural to urban. This situation developed an area in between urban and rural knows as peri-urban area which increase in number and typologies. Peri-urban continues to grow spatially and in popula-tion, thus these zones have unique identities which continue to evolve. Thus, the aim of this article is to explore the importance of socio-cultural landscape at Kuala Selangor as urban peripheries and how it could establish the identity for the future of a good environment. Providing a socio-cultural approach to the peri-urban notion, this paper discovers through the literature study the subjective dimension on the socio-cultural definition at the peri-urban area, in order to understand its ‘unique identity’. In this article, the notion of ‘socio-cultural landscape’ is presented in arrange to investigate the ambiguity that exists within these days peri-urban area with respect to their social and unique presence. The paper is based on an extensive literature review to distinguish the significance of socio-cultural landscape for peri-urban areas in regards to revive its image and identity.
Keywords: socio-cultural; urban sprawl; peri- urban; urbanization; identity